Pro PerformancePoint Server 2007: Building Business Intelligence Solutions - Janus, Philo (Apress, 2012)
“Business intelligence” is a nebulous, scary term that is often brandished as something that you need an MBA and 20 years of experience in the field to implement. As I’ve dug my way around the field in the three short years since Business Scorecard Manager was released, what I’ve found is that the technology does not have to be that hard. I’m not saying it’s always easy, but it’s definitely approachable and accessible to the average developer or DBA.: